Trends in Contemporary Legal Development: A Narrative Review - Rizki, Muhammad; Anshori, Ibnu; Mufida, Alfi (International Journal of Sustainable Law, 2025)
The development of law today reflects significant and complex dynamics driven by rapid technological transformation, social change, and the growing need for adaptive regulation in the digital era. Despite the increasing adoption of digital courts, enhanced data protection regulations, and the integration of artificial intelligence (AI) in legal practice, existing literature indicates limited comprehensive analyses that map these trends in a holistic manner (Gap). This narrative review synthesizes findings from academic publications, policy reports, and recent legal discourse to provide a thorough understanding of contemporary legal developments (Evidence). The review identifies that global legal systems are moving towards automation, transparency, and the protection of digital rights, while simultaneously facing challenges such as algorithmic bias, privacy threats, and disparities in legal access. Based on these insights, this study proposes the need for a responsive, sustainable, and inclusive legal framework that aligns technological innovation with principles of justice and human rights (Proposal). The findings highlight the crucial role of legal scholars and practitioners in shaping laws that can adapt to the complexities of the digital age.